On the Role of Magnetic Field Fluctuations in Diffusive Shock Acceleration - The, Doan Kim; Anh, Pham Tuan; Diep, Pham Ngoc; Dong, Pham Ngoc; Hiep, Nguyen Van; Hoai, Do Thi; Nhung, Pham Thi Tuyet; Thao, Nguyen Thi; Darriulat, Pierre (Communications in Physics, 2011)
A simple numerical simulation of the mechanism of diffusive shock acceleration, responsible for the acceleration of cosmic rays in the environment of young Super Nova Remnants, is presented. The relative roles of a uniform magnetic field component, inherited from the parent collapsed star, and of magnetic turbulences, known to be present in the vicinity of the shock, are investigated. It is shown that a uniform magnetic field allows for only doubling the energy of the cosmic particle. Important accelerations require the simultaneous presence of magnetic field turbulences at a scale commensurable with its Larmor radius.